Ratios of dijet production cross sections as a function of the absolute difference in rapidity between jets in proton-proton collisions at root s=7 TeV - Chatrchyan, S; Khachatryan, V; Sirunyan, A; Tumasyan, A; Adam, W; Bergauer, T; Dragicevic, M; Eroe, J; Fabjan, C; Friedl, M; Fruehwirth, R; Ghete, V; et al. (2012)
A study of dijet production in proton-proton collisions was performed at √s = 7TeV for jets with pT>35 GeV and pipeypipe<4. 7 using data collected with the CMS detector at the LHC in 2010. Events with at least one pair of jets are denoted as "inclusive". Events with exactly one pair of jets are called "exclusive". The ratio of the cross section of all pairwise combinations of jets to the exclusive dijet cross section as a function of the rapidity difference between jets {pipe}Δypipe is measured for the first time up to {pipe}Δypipe=9. 2. The ratio of the cross section for the pair consisting of the most forward and the most backward jet from the inclusive sample to the exclusive dijet cross section is also presented. The predictions of the Monte Carlo event generators pythia6 and pythia8 agree with the measurements. In both ratios the herwig++ generator exhibits a more pronounced rise versus {pipe}Δypipe than observed in the data. The BFKL-motivated generators cascade and hej+ariadne predict for these ratios a significantly stronger rise than observed. © 2012 CERN for the benefit of the CMS collaboration.